Razvoj kočevske čitalnice med letoma 1919-1941 - Južnič, Stanislav (Knjižnica, 2004)
The paper presents the founding of the first Slovene library in Kočevje and its development during the national quarrels with the German inhabitants of the area. The Slovene Reading Society was transformed form the Yugoslavian oriented society with broad cultural ambitions into one of the most important organizations in town. The main working area of the Society became the libraryand this was in the beginning just one of its various activities.
Keywords: knjižnice; čitalnice; Kočevje; zgodovinski pregledi; 1919/1941